Involvement of the persistent Na+ current in the diastolic depolarization and automaticity of the guinea pig pulmonary vein myocardium - Masahiko Irie; Haruhito Hiiro; Shogo Hamaguchi; Iyuki Namekata; Hikaru Tanaka (Elsevier, 2019)
The role of the Na+ current in the automaticity of the pulmonary vein myocardium was examined in isolated guinea pig pulmonary vein cardiomyocytes and tissue preparations. Tetrodotoxin inhibited the automaticity of pulmonary vein tissue preparations by suppressing the diastolic depolarization of the action potential. ATX-II, which increased the density of persistent component of the Na+ current (late INa), induced a depolarization of the resting membrane potential followed by spontaneous firing of action potentials. GS-458967, which inhibited the late INa, suppressed the diastolic depolarization and the firing of action potentials. Pilsicainide, which inhibited only the transient component of Na+ current (peak INa), had no effect on the firing frequency. GS-458967 had no effect on the contractile force of the working myocardium. In conclusion, late INa is involved in the diastolic depolarization and automaticity of the pulmonary vein myocardium. Late INa inhibitors appear to be effective therapeutic agents for atrial fibrillation with minimum adverse effects on the working myocardium. Keywords: Pulmonary vein, Automaticity, Diastolic depolarization, Late INa, GS-458967